THE COUNCIL OF TRENT: WAS IT OPEN TO THE SPIRIT OF GOD? - MATTAM, JOSEPH (Asian Horizons, 2017)
The situation of the Catholic Church prior to the Reformation was really deplorable. The rot was widely spread from the top to the bottom; Popes and Bishops were not really serving the Church and the people but were interested in bettering their own economic conditions. Besides the concubinage of the clergy, there were so many areas that had deviated from the Gospel and the teachings of Jesus. The indulgences which grew in the sacrament of confession as a lenience shown to the sinner, became a money making instrument which led the Church to become totally corrupt. Hence one may rightly say the call for Reform was really the work of the Spirit of God. The article suggests that the leaders of the Catholic Church do not seem to have listened to the Spirit; they do not seem to have taken the Reformers’ call for reform seriously. If they had listened to the Reformers in a Christian spirit of openness, and called them for dialogue, a split in the Body of Christ could have been averted and the Church would have been given a chance to grow in a united way to the benefit of all. Hence the article raises the question as suggested in the title. It is merely a suspicion that is voiced here, not an absolute statement of fact; the article invites further reflections from scholars.